JOURNALISTIC COVERAGE OF A POLITICAL SCANDAL IN DEMOCRACY: Vaza Jato in Folha de S.Paulo - Araujo, Renan; Belim, Célia (Brazilian journalism research, 2024)
ABSTRACT – The article aims to identify the narratives and understand the news, the editorial discourse, and the decisions of Folha de S.Paulo that defend the publication of Vaza Jato and reveal quality journalism practices. The mixed method includes narrative and discourse analyses and interviews. The results show the presence of three narratives linked to accusations against Judge Moro and prosecutors, validation of message veracity, and criticism of Lava Jato. The discourse and the interview emphasize that direct access to the conversations, confirmation of the veracity and public interest of these conversations, and the context influenced the publication. RESUMO – O artigo pretende identificar as narrativas e perceber o discurso noticioso e editorial e as decisões da Folha de S.Paulo que defendem a publicação da Vaza Jato e revelam práticas de jornalismo de qualidade. O método misto inclui análise narrativa e de discurso e entrevista. Os resultados mostram a presença de três narrativas ligadas a acusações contra Moro e procuradores, validação da veracidade das mensagens e críticas à Lava Jato. O discurso e a entrevista realçam que o acesso direto às conversas, a confirmação de veracidade e o interesse público dessas conversas e o contexto influenciaram a publicação. RESUMEN – El artículo pretende identificar las narrativas y comprender el discurso y las decisiones informativas y editoriales de Folha de S.Paulo que defienden la publicación de Vaza Jato y revelan prácticas periodísticas de calidad. El método mixto incluye análisis narrativos y discursivos y entrevistas. Los resultados muestran la presencia de tres narrativas vinculadas a las acusaciones contra Moro y los fiscales, la validación de la veracidad de los mensajes y las críticas a Lava Jato. El discurso y la entrevista destacan que el acceso directo a las conversaciones, la confirmación de la veracidad y el interés público de las mismas y el contexto influyeron en la publicación.